Perubahan Pemahaman Mahasiswa Program Studi Pendidikan Bahasa Jepang Terhadap Rencana Pelaksanaan Pembelajaran Pasca Pelaksanaan Plp - Lestari, Bunga Citra; Basri, Merri Silvia; Budiani, Dini (Jurnal Pendidikan Indonesia, 2022)
This study aims to determine the understanding of Japanese Language Education Study Program students' understanding of the learning device components in the form of learning implementation plans before and after the implementation of the school field introduction and to understand the learning device components in the form of learning implementation plans after the implementation of the school field introduction. The type of research used is descriptive research with a qualitative approach. The data obtained based on the research are primary data and secondary data with data acquisition in the form of interviews and documentation. The test subjects were Japanese language study program students who had carried out an introduction to the school field. The results of the study were obtained in the implementation of the school field introduction, the data source was able to determine the components in the learning implementation plan that adapted to the character of the students and the conditions of the class and school where the data source carried out the school field introduction and there were changes in the allocation of time, determining learning objectives, and determining methods learning. Thus it can be concluded that students of the Japanese Language Study Program have received a change in understanding in the components of making a lesson plan after attending an introduction to the school field.